The role of executive functions in predicting math academic skills of mentally retarded elementary students - Zahra Nasiri; Hamdollah Manzari Tavakoli; Amanollah Soltani; Anahita Bahreyni (Payame Noor University, 2024)
The reason for failure in learning and academic failure is the lack of academic skills. Mentally retarded children, as a special and vulnerable group of society, usually have little academic skills for various reasons. One of the important reasons can be executive functions. The present research was conducted with the aim of investigating the role of executive functions in predicting the mathematical academic skills of mentally retarded elementary students. The descriptive research method was correlation type. The statistical population was all 995 mentally retarded students of the elementary level in the academic year 1402-1401 in Kerman city; Based on the Morgan-Karjesi table, the statistical sample size of this research was 278 people; which were selected by stratified random sampling method. Brief executive function questionnaire and math teacher-made test were used to collect data. Data analysis was done with spss25 and Amos24 software. The results of the research showed that the model of the role of executive functions in predicting math academic skills in mentally retarded primary school students has an acceptable fit by controlling the effect of intelligence and age. There was a significant relationship between inhibition, attention transfer, emotional control, initiation, working memory, planning, organization of materials and revision with mathematical academic skills of intellectually disabled students, so that the components of executive functions simultaneously accounted for 0.357 of skill variance. The academic skills of intellectually disabled students were explained and the most important predictors of mathematical academic skills in intellectually disabled students were planning and working memory respectively